The Potential Of Halal Industry In Indonesia To Support Economic Growth - Mujahidin Mujahidin (Al-Kharaj: Journal of Islamic Economic and Business, 2020)
Indonesia as the largest Muslim-populated country in the world has the potential for the development of the halal industry, but the fact said, where Indonesia is left from other countries such as Malaysia in the development of the halal industry. In the year 2017 Indonesia was ranked 11th, in 2018 Indonesia fixed its position to 10th place, in 2019 Indonesia to improve its ranking to position 4 it is obvious that Indonesia is potentially a center Halal industry in the world. Indonesia has established a national commission of Sharia, which will focus on improving the halal industry in Indonesia. Halal industry developed from two sectors namely products and services. From the product, sectors are food and beverage, fashion, cosmetics whereas from the sector of services, namely, banking, tourism, media, and entertainment